Relação entre padrão respiratório e dados espirométricos em pneumopatas crônicos. - LIMA, Renato Miranda (2023)
Introduction: The impact of breathing pattern in the workload of the respiratory muscles is a controversy still unresolved and it is important for the treatment of patients with lung diseases as well as the failure of the chest muscle. The ventilatory response in patients with chronic obstructive pulmonary disease (COPD) is characterized by a rapid and shallow than that of healthy people during exercise. Objectives: To describe and analyze the relationship between breathing pattern and spirometric data of patients with chronic lung diseases, as well as separately in patients with asthma and COPD. Methods: It was conducted a cross-sectional study with a descriptive and analytical character with 100 patients over 18 years of age, treated at the Pulmonology Clinic of the University Hospital João de Barros Barreto with bronchial asthma and COPD in the period from May to July 2011 analyzing gender, age, education, occupation, origin, life style and personal history, presence or absence of symptoms related to the respiratory system, respiratory pattern and spirometric data. Results: The majority were female, had 60 years or more, was a native of Pará, with a predominance coming of Belém, 53% of patients had a profession, about two thirds had an incomplete primary education, 57% one to two health antecedents, almost 90% had no environmental control. More than half reported cough, dyspnea, and 42% fatigue, almost half were ex-smokers, two thirds had decreased respiratory amplitude and one third with barrel chest. Almost 75% had costal breathing pattern, with the percentage of PRE-BD FEV1 compared with the predicted having statistical significance in the relationship under study (spirometry versus breathing pattern). 41% of patients had bronchial asthma and costal breathing pattern, existing significance into the same variable of the overall study population. 32% had COPD and costal breathing pattern, with no signficance in any variable studied in the relationship under study. Conclusion: Most patients have costal breathing pattern, placing them in a category subject to modification of standard muscle training in respiratory therapy. We observe a possible relationship between the use of abdominal muscles in the composition of the breathing pattern of asthmatic patients and better performance on spirometric variable that classifies the severity of the disease. No such relationship was observed in patients with COPD.